2015
DOI: 10.1021/acs.est.5b00412
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methane Emissions and Vehicle Efficiency on the Climate Implications of Heavy-Duty Natural Gas Trucks

Abstract: While natural gas produces lower carbon dioxide emissions than diesel during combustion, if enough methane is emitted across the fuel cycle, then switching a heavy-duty truck fleet from diesel to natural gas can produce net climate damages (more radiative forcing) for decades. Using the Technology Warming Potential methodology, we assess the climate implications of a diesel to natural gas switch in heavy-duty trucks. We consider spark ignition (SI) and high-pressure direct injection (HPDI) natural gas engines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…If new technology can indeed narrow the efficiency penalty from 20% to 10%, CNG would achieve a baseline emission rate nearly identical to diesel. Our results are consistent with a recent study that found the 100-year GHG impacts of CNG and diesel trucks to be very similar, with the ranking depending on the assumptions for efficiency penalty (the study considered a 0-20% range) and natural gas leak rate (0-4% range) [Camuzeaux et al, 2015].…”
Section: Comparisons Within Sectorssupporting
confidence: 92%
“…If new technology can indeed narrow the efficiency penalty from 20% to 10%, CNG would achieve a baseline emission rate nearly identical to diesel. Our results are consistent with a recent study that found the 100-year GHG impacts of CNG and diesel trucks to be very similar, with the ranking depending on the assumptions for efficiency penalty (the study considered a 0-20% range) and natural gas leak rate (0-4% range) [Camuzeaux et al, 2015].…”
Section: Comparisons Within Sectorssupporting
confidence: 92%
“…The measured Barnett methane leakage is low enough that gas fired electricity in this region causes less climate forcing than coal-fired electricity (see the SI Appendix for details, including effect of CH 4 mitigation). By contrast, use of compressed natural gas sourced in the Barnett instead of diesel for freight trucks would cause greater forcing for several decades (1,39,40).…”
Section: Methane Emissions Are Significantly Higher Than Estimates Bamentioning
confidence: 99%
“…Looking to the individual parameters of Scenario 4 and the individual managerial decisions to be made, we suggest that this CH 4 -emitting effect can only be reduced if engine efficiency of heavy duty vehicles in the combustion of compressed natural gas are improved. Secondly, this CH4 emitting effect can also be reduced if leaking methane emissions through the drilling and extraction of natural gas is reduced in the supply chain of the fuel (Camuzeaux et al, 2015;Brandt et al, 2014). Figure 5 illustrates the total energy consumed by the supply chains in all four of the scenarios considered, and Figure 6 shows the total emissions from the life cycle stages of each scenario.…”
Section: [Insert Figures 3 and 4 Here]mentioning
confidence: 99%